PEMETAAN HUBUNGAN GREEN FINANCE DAN FIRM PERFORMANCE: KAJIAN SYSTEMATIC LITERATURE REVIEW - Wati, Cicik Retno; Kurniasari, Irma (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2025)
This study aims to map scientific developments and identify future research gaps in the areas of green finance and firm performance. The research method employed is a systematic literature review (SLR) with a bibliometric approach, assisted by R software, on 533 documents published in Scopus between 2016 and 2025. The analysis includes mapping publication trends, citations, research countries, key journals, and emerging research topics. The results show that publications on this theme experienced significant growth in 2021, with the countries contributing the most research being China, followed by India, and Malaysia. Dominant topics include green innovation, environmental performance, green bonds, and green finance policies. The results of this study indirectly provide an overview of the conceptual framework linking green finance instruments to corporate performance dimensions and offer a future research agenda. This research is expected to provide theoretical contributions in the form of a concept map of current scientific knowledge, as well as practical implications for regulators, financial institutions, and corporate managers.